2019
DOI: 10.1007/jhep01(2019)053
|View full text |Cite
|
Sign up to set email alerts
|

Audible axions

Abstract: Conventional approaches to probing axions and axion-like particles (ALPs) typically rely on a coupling to photons. However, if this coupling is extremely weak, ALPs become invisible and are effectively decoupled from the Standard Model. Here we show that such invisible axions, which are viable candidates for dark matter, can produce a stochastic gravitational wave background in the early universe. This signal is generated in models where the invisible axion couples to a dark gauge boson that experiences a tach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 47 publications
(61 reference statements)
10
130
0
Order By: Relevance
“…Here, we give a brief overview of the model presented in Ref. [8], which consisted of an axion field ϕ and a massless dark photon X μ of an unbroken Uð1Þ X Abelian gauge group,…”
Section: The Audible Axion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we give a brief overview of the model presented in Ref. [8], which consisted of an axion field ϕ and a massless dark photon X μ of an unbroken Uð1Þ X Abelian gauge group,…”
Section: The Audible Axion Modelmentioning
confidence: 99%
“…In Ref. [8], we showed that axions or axionlike particles coupled to a light dark photon can produce a stochastic gravitational wave background (SGWB) when the axion field begins to oscillate in the early Universe, allowing exploration of parameter space inaccessible to experiments that rely on the axion-photon coupling. The rolling axion induces a tachyonic instability that amplifies vacuum fluctuations of a single gauge boson helicity, sourcing chiral GWs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, axionlike particles are abundant in string compactifications [14][15][16]. This motivates searching for axions on different fronts, including using a variety of techniques to directly detect axions [17], as well as collider probes [18][19][20][21][22], gravitational wave searches [23][24][25][26], and astrophysical searches [27].…”
Section: Introductionmentioning
confidence: 99%
“…(1.2), for f a O(10 12 ) GeV, the universe is overclosed unless θ mis is sufficiently small (applicable only to the case of pre-inflationary PQ breaking). There exist late-time mechanisms such as dilution from entropy production by late decaying moduli fields [31,32] or the axion superpartner [33][34][35][36][37], and depletion to other species [38][39][40][41]. Meanwhile, it is crucial to explore natural explanations to a small θ mis .…”
Section: Introductionmentioning
confidence: 99%